2021
DOI: 10.1002/pa.2601
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease 2019 (COVID‐19) and individuals with intellectual and developmental disabilities in Nigeria

Abstract: This article chronicles the present situation of coronavirus disease 2019 (COVID‐19) on individuals with intellectual and developmental disabilities (IDD) in Nigeria. A systematic search was conducted on three bibliographic databases: MEDLINE Complete, Web of Science and Scopus, and supplemented with grey literature searches to assess studies on the effect of COVID‐19 on these individuals in Nigeria with data on this group from December 2019 to July 2020. There were no studies found concerning individuals with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Second, all included studies were conducted in HICs, which may have introduced bias and limited the generalisability of the findings. In most cultures, IDD is accompanied by marginalisation and stigmatisation [ 125 , 126 ]. It would be interesting to examine what extent the QoL of adults with DS via self-and proxy reports is universally bound.…”
Section: Discussionmentioning
confidence: 99%
“…Second, all included studies were conducted in HICs, which may have introduced bias and limited the generalisability of the findings. In most cultures, IDD is accompanied by marginalisation and stigmatisation [ 125 , 126 ]. It would be interesting to examine what extent the QoL of adults with DS via self-and proxy reports is universally bound.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of this review is the lack of quality appraisal of the papers included. Although scoping reviews do not aim to assess the quality of the evidence (see [24]), in light of the emerging nature of ID research in Nigeria, we did not carry out one, because we wanted to be able to access the available studies relevant for this scoping review notwithstanding their methodological strength and rigor. We acknowledge and corroborate McKenzie, McConkey and Adnams' [3] recommendation that there is a need for improvement in "disability data collection" in Africa in the context of reporting, methodological rigor and robustness.…”
Section: Limitationsmentioning
confidence: 99%
“…The literature has consistently acknowledged the scarcity of information and empirical research about people with ID in developing countries such as Nigeria, e.g., [2,4,24]. For example, a recent meta-synthesis [6] of disability research in Western Africa revealed that, of the 223 disability articles from West Africa reviewed, only 24 were papers related to people with ID in the whole of West Africa; however, there was no information from the meta-synthesis on how many of these 24 ID studies were specifically derived from Nigeria [6].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 has a multi-dimensional effect on various organs of the body and has also generated a plethora of psychiatric manifestations across the different strata of the society [ 21 ]. The importance of disease outcomes in relation to the individual’s social integration has been known to interfere with a person’s quality of life [ 21 ]. Thus, the interest in health-related quality of life of patients who have been affected by the condition increased, during the pandemic and afterwards.…”
Section: Introductionmentioning
confidence: 99%